Green School and Environmental Education at Junior High School: A Bibliometric Analysis - Putera, Adhy Setia; Maarif, Samsul; Bandarsyah, Desvian; Mulyono, Herri (Journal of Cultural Analysis and Social Change, 2025)
This study analyzes research on environmental education and the implementation of green school principles at the junior high school level, focusing on trends, challenges, and future directions. A bibliometric approach was applied using Google Scholar as the main database, covering journal articles published between 2013 and 2023. Data were analyzed with VOSviewer to map citation patterns, keyword clusters, and collaboration networks, while PRISMA ensured systematic selection. The findings reveal an increasing number of publications, with three dominant clusters: pedagogical implementation in formal education, the role of geographical and policy contexts, and psychological-behavioral impacts such as environmental awareness, green consumption, and environmental protection. Despite progress, challenges remain, including limited resources, insufficient teacher training, and lack of supportive policies. The study concludes that environmental education at the junior high school level is essential for fostering sustainability awareness and responsible behavior, requiring an integrative approach that combines pedagogy, policy, and psychology. Practical implications emphasize digital learning tools and community-based projects to enhance student engagement and improve green school initiatives.